2017
DOI: 10.1152/advan.00117.2016
|View full text |Cite
|
Sign up to set email alerts
|

A survey of first-year biology student opinions regarding live lectures and recorded lectures as learning tools

Abstract: A cohort of first-year biology students was surveyed regarding their opinions and viewing habits for live and recorded lectures. Most respondents (87%) attended live lectures as a rule (attenders), with 66% attending more than two-thirds of the lectures. In contrast, only 52% accessed recordings and only 13% viewed more than two-thirds of the available recordings. Respondents regarded lectures as efficient for information delivery (75%), and 89% enjoyed live lectures because they were useful for learning (89%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
1
17
1
2
Order By: Relevance
“…The nding of an association between accessing lecture recording and academic outcomes involving lecture content is not in line with most previous studies. Thus, most previous studies of students of the biological sciences have shown no association between accessing lecture recordings and academic performance [6,11,15,16,19,21,22], or a negative association [17,23,24].…”
Section: Associations Between Lecture Recording Access and Academic Omentioning
confidence: 93%
See 2 more Smart Citations
“…The nding of an association between accessing lecture recording and academic outcomes involving lecture content is not in line with most previous studies. Thus, most previous studies of students of the biological sciences have shown no association between accessing lecture recordings and academic performance [6,11,15,16,19,21,22], or a negative association [17,23,24].…”
Section: Associations Between Lecture Recording Access and Academic Omentioning
confidence: 93%
“…Most studies have shown no association between accessing lecture recordings and academic performance [11,15,16,[19][20][21][22]. Other studies have shown that the use of lecture recordings to be negatively [17,[23][24][25] or positively [19] associated with academic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I mange av de tidligere publiserte studiene er en opptatt av hvilke holdninger studenter og forelesere har til bruken av filmede forelesninger. Disse studiene viser at studentene generelt er positive til å få tilgang til slike opptak og ønsker mer av det (Bassili & Joordens, 2008;Copley, 2007;Danielson, Preast, Bender, & Hassall, 2014;Heilesen, 2010;Morris, Swinnerton & Coop, 2019;Simcock, Chua, Hekman, Levin & Brown, 2017). Et viktig argument fra studentenes side er at de får mulighet til å se forelesningene på nytt, som støtteverktøy til egenstudier.…”
Section: Studentenes Og Forelesernes Holdningerunclassified
“…De fant at studenter med lave karakterer brukte filmopptak i større grad enn studenter med høye karakterer. Tilsvarende fant Simcock et al (2017) at karakterene til studentene var positivt korrelert med antall forelesninger de deltok i, og negativt korrelert med antall filmopptak studentene hadde sett. Lignende funn kan vi finne hos Owston, Lupshenyuk og Wideman (2011) og Johnston, Massa, og Burne (2013), hvor en finner negativ sammenheng mellom bruk av filmede forelesninger og prestasjon.…”
Section: Filmede Forelesninger Og Laeringunclassified